The effects of mass transfer on drop breakage in rotating disc contactors - Ali, Noorhalieza; Slater, M. J. (1991)
Breakage of single drops of solvent in water is examined in a 300 mm diameter RDC. Correlations for drop size distribution and scale up effects obtained from breakage without mass transfer are used to find apparent interfacial tensions for breakage with mass transfer occurring.